Design of Ph Level Monitoring Tool in Coating Process at PT XYZ Using QFD Method - Betara Churraera; Wiyono Sutari; Sheila Amalia Salma (Jurnal Rekayasa Sistem & Industri, 2022)
PT XYZ is a company engaged in the furniture industry, the products produced are various, one of which isthe Yamato folding chair. Yamato folding chairs are the most produced products, the production process ofYamato folding chairs consists of three processes, namely the construction process, the nickel chromeplating process, and the assembly process. In this study, the researchers focused more on the nickel chromeplating process because the most defects were in this process based on historical data from July 2020 toDecember 2021. The nickel plating process also has many types of defects including streaks, burns, yellow,and so on. Nickel chrome plating process is a metal deposition process on the surface of a metal or nonmetal electrolytically. In the analysis of the problem there is a process that is not fulfilled using the Ishikawadiagram, 5 whys analysis, and FMEA it is known that the influential factor is the incompatibility of pH levels,to correct these problems, a tool is designed. The method used for the design of the tool is the QFD (QualityFunction Deployment) method. QFD is a way to improve the quality of products and services byunderstanding each consumer's needs, then connecting them through technical aspects to produce productsor services that suit consumer needs in each manufacture product or service produced. The results of thisstudy are a tool to monitor pH levels so that they are in standard conditions. With the design of a monitoringtool for pH levels, it is expected to minimize defects that occur in the coating process.